Manual on the recognition, documentation and reporting of torture - Parong, Aurora C A.; Medical Action Group, Inc.; Commission on Human Rights of the Philippines (Quezon City Medical Action Group, Inc., 2005)
This manual is intended to serve as guidelines for the assessment of alleged torture victims, for the effective documentation of torture and other inhuman treatment, and for the reporting of alleged torture cases to the proper investigative body.
Chapter 1 : Understanding torture -- Chapter 2 : Medical and allied professionals' duties and responsibilities against torture -- Chapter 3 : General documentation of torture -- Chapter 4 : General types, forms, and sequelae of torture -- Chapter 5 : Medical documentation of torture -- Chapter 6 : Providing care for women, survivors of torture -- Chapter 7 : Torture among children -- Chapter 8 : Torture prohibitions and remedies -- Chapter 9 : Reporting mechanisms -- Annex 1 : Anatomical drawings for the documentation of torture and ill-treatment
Keywords: Torture -- Prevention -- Handbooks, manuals, etc; Torture -- Moral and ethical aspects; Human Rights